The Oxford companion to British history - Cannon, John Ashton (New York : Oxford University Press, 1997)
100 distinguished contributors describe & analyse people and events that have shaped and defined life in Britain over 2000 years.
Machine derived contents note: List of Contributors; Acknowledgements; Introduction; Note to the Reader; Index of Topics; 4000+ A-Z entries; 12 maps.
Includes and index.
Includes index.
Keywords: Great Britain -- History -- Encyclopedias; Great Britain - History - Encyclopedias